Doangang Pattuik Pakrisik Battang Sebagai Media Pengobatan Masyarakat Desa Rappolemba (Suatu Tinjauan Semiotika Riffaterre) - Ismail Ismail; Asia M. (Indonesian Journal of Social and Educational Studies, 2022)
This study aims to describe the meaning of Doangang Pattuik Pakrisik Battang as a Medicinal Media for the Rappolemba Village Community based on heuristic readings. This type is descriptive qualitative. The data in this study is Doangang Pattuik Pakrisik Battang which is the primary data used in the treatment process based on the informants. Riffaterre's Semiotics theory in this case heuristic reading is used to examine the text in Doangang Pattuik Pakrisik Battang to describe the meaning of the text Doangang Pattuik Pakrisik Battang. The collection techniques are data, data reduction, data presentation and then drawing conclusions. The object of this research is the text of Doangang Pattuik Pakrisik Battang which is analyzed based on the heuristic reading of Riffaterre's theory of Semiotics. The results of this study found that there were only six treatments analyzed based on heuristic readings showing that found in some words that were not linguistically structured then the addition of embedded words aimed to produce a meaning according to grammar in general which clarified the meaning to be conveyed.Keywords: Meaning, doangang pattuik pakrisik battang, Rifaterre Semiotics, Heuristics